What Does It Take to Work in the Translation Profession in Canada in the 21st Century? Exploring a Database of Job Advertisements - Bowker, Lynne (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis article contains an investigation into the translation profession in Canada in the 21st century. The aim of this study is to investigate translation from the perspective of those who employ translators by analyzing a database of job advertisements for a variety of translation-related positions that were collected between January 2000 and December 2002. Spurred on by the effects of globalization, the language industry is in a period of change. Based on empirical evidence collected from the database, this article attempts to evaluate the current state of the profession in Canada and to determine what employers are seeking.